Sister Mary Joseph Nodule in an Ovary Adenocarcinoma - Poparic, Selma (Med Arch, 2017)
INTRODUCTION: Sister Mary Joseph Nodule (SMJN) is a metastatic umbilical lesion secondary to a primary malignancy of any viscera, stomach and colon being most common in men, and ovary in women. CASE REPORT: In this article, we present the case of SMJN in a 54-year old female patient. An urgent diagnostic workup was performed with a computerized tomography of abdominal cavity and pelvis showing an expansive tumorous formation covering uterus with a carcinomatosis of peritoneum. After biopsy, immunohistochemical profile suggested adenocarcinoma of the ovarian origin. The patient was then referred to the Oncology Consilier of Gynecology Department and further continued followed by the Oncology team.